Industry Value: Empirical Study of Factors Affecting - Hanifah, Risti Ulfi; Sugiyanto, Eviatiwi Kusumaningtyas; Triyani, Dian (Universitas Semarang, 2021)
The purpose of this research is to analyze the factors that influence the value of the industry. The independent variables are investment opportunities, dividend policy, financial leverage, profitability. The population in this research is a non-financial industry listed on the IDX from 2017 to 2019. The illustrations for this research were selected using a purposive sampling procedure, and 200 illustrations were taken. Information analysis uses multiple regression procedures. The results of this research show that financial leverage, profitability and an independent board of commissioners affect the value of the industry, on the other hand, investment opportunities do not affect the value of the industry.